Pengaruh Transparansi Pengelolaan Zakat Terhadap Minat Muzakki Desa Paluh Manis Kecamatan Gebang Membayar Zakat Pada Baznas Kabupaten Langkat - Supratman Supratman; Rani Febriyanni; Asmawarna Sinaga (Universitas 17 Agustus 1945 Semarang, 2023)
The research aims to determine the effect, the magnitude of the influence, and the relationship between the transparency of zakat management on the interest of muzakki in Paluh Manis Village, Gebang District, to pay zakat at BAZNAS, Langkat Regency. The data source for this research was obtained from questionnaire answers given by research respondents, namely the people of Paluh Manis Village, Gebang District, who paid zakat at BAZNAS, Langkat Regency, as many as 56 respondents. Data analysis in this study used validity test, reliability test, classic assumption test, hypothesis test, and simple linear regression analysis. Based on this test, it is explained that there is a significant influence between the transparency of zakat management on the interest of the people of Paluh Manis Village, Gebang District, to pay zakat at BAZNAS, Langkat Regency. smaller than 0.05 or (0.000 <0.05) and tcount > ttable (4.382 > 2.00488) so there is an influence of variable X on variable Y. Transparency of zakat management affects the interest of the people of Paluh Manis Village, Gebang District, to pay zakat at BAZNAS, Langkat Regency by 24.9%. There is a positive or parallel relationship between the transparency of zakat management and the interest of the people of Paluh Manis Village, Gebang District, to pay zakat at BAZNAS, Langkat Regency.